An Overview on Issues of Wind Energy Conversion Systems (International Journal of Food and Nutritional Sciences, 2022)
In the last ten years, wind power capacity has increased dramatically. Many loads (such as isolated settlements, islands, ships, and so forth) are not connected to the main grid. They need a stand-alone generating system to supply local electrification (which can maintain a steady nominal voltage and frequency) This research looks at wind energy conversion systems (WECs), wind energy converter system (WECs) characteristics, horizontal axis wind turbines (HAWT), vertically axis wind turbines (VAWT), and wind energy conversion system difficulties. The development of unique stand-alone generating technologies has been motivated by this necessity. First, a summary of different existing generator technologies for grid-connected operations is presented.